A case-control study on the relationship between miRNAs single nucleotide polymorphisms and sepsis risk. Issue 33 (August 2019) - Zhang, Yan; Li, Min; Bao, Lanying; Hu, Pengfei
Abstract : Abstract: MicroRNAs (miRNAs) play an important role in the pathogenesis of sepsis, but the association of miRNAs single nucleotide polymorphisms (SNPs) and sepsis risk is not clear. We analyzed plasma levels of miR-187, miR-21, and miR-145 in 180 patients with sepsis and 180 healthy controls were analyzed, and the SNPs: rs12605436, rs13137, and rs353291 were detected by sequencing. Plasma levels of tumor necrosis factor (TNF)-α and interleukin (IL)-6 were measured in all subjects by enzyme-linked immunosorbent assay (ELISA). The results showed that the levels of TNF-α and IL-6 in the plasma of patients with sepsis were significantly higher than those in patients of the control group ( P  < .0001). Plasma levels of miR-187 in patients with sepsis were significantly lower than those in the control group, while those of miR-21 and miR-145 were significantly higher than those in the control group ( P  < .0001). Plasma levels of miR-187 in sepsis patients were inversely correlated with those of TNF-α and IL-6 ( r  = −0.2841, −0.2163), and plasma levels of miR-21 and miR-145 were positively correlated with those of TNF-α and IL-6 ( r  = 0.615, 0.3057, 0.4465, 0.2734). The T allele of the miR-187 SNP rs12605436 was found to be a risk factor for sepsis (OR = 1.403, 95% CI = 1.205–1.612, P  < .001). The T allele of the miR-21 SNP rs13137 and the T allele of the miR-145 SNP rs353291 (OR = 0.685, 95% CI = 0.566–0.820, P  < .001) were found to be a protective factor for sepsis (OR = 0.755, 95% CI = 0.632–0.896, P  < .001). From our results, we can see that the plasma levels of miRNAs containing the SNPs rs12605436, rs13137, and rs353291 are associated with the occurrence of sepsis.